Financial Performance Analysis Based on Activity Ratios and Profitability Ratios in Food and Beverage Industry Companies Listed on the Indonesia Stock Exchange (IDX) for the Period 2016 – 2020 - Fitrah (Pustaka Digital Indonesia, 2023)
This research aims to identify the financial performance of companies in the food and beverage industry listed on the Indonesia Stock Exchange during the period from 2016 to 2020. This study uses a quantitative descriptive method and relies on secondary data obtained from financial reports. The sample in this research consists of 5 companies selected based on specific criteria using the Purposive Sampling technique. Based on the analysis of the financial reports of companies in the food and beverage sector listed on the Indonesia Stock Exchange during the period from 2016 to 2020, involving the use of financial ratios such as activity and profitability ratios, it can be concluded that the average ratio values of the 8 companies in the food and beverage sector listed on the Indonesia Stock Exchange during the period from 2016 to 2020 indicate that the condition of these companies is not favorable. The Activity Ratio analysis, measured by Total Asset Turnover and Inventory Turnover, indicates that companies in the food and beverage industry can be categorized as being in an unfavorable condition because they are still below industry standards. This suggests that these companies have not achieved a sufficient level of stability and efficiency in their operational activities to generate income. Meanwhile, Profitability Ratio analysis, measured by Net Profit Margin, Return On Asset, and Return On Investment, also indicates that companies in the food and beverage industry can be categorized as being in an unfavorable condition because their financial performance is still below industry standards. This means that these companies have not been able to generate adequate profit or return from their sales or from their own capital.